Human textiles: A cell-synthesized yarn as a truly "bio" material for tissue engineering applications. (15th March 2020) - Magnan, Laure; Labrunie, Gaëlle; Fénelon, Mathilde; Dusserre, Nathalie; Foulc, Marie-Pierre; Lafourcade, Mickaël; Svahn, Isabelle; Gontier, Etienne; Vélez V., Jaime H.; McAllister, Todd N.; L'Heureux, Nicolas
Abstract: In the field of tissue engineering, many groups have come to rely on the extracellular matrix produced by cells as the scaffold that provides structure and strength to the engineered tissue. We have previously shown that sheets of Cell-Assembled extracellular Matrix (CAM), which are entirely biological yet robust, can be mass-produced for clinical applications using normal, adult, human fibroblasts. In this article, we demonstrate that CAM yarns can be generated with a range of physical and mechanical properties. We show that this material can be used as a simple suture to close a wound or can be assembled into fully biological, human, tissue-engineered vascular grafts (TEVGs) that have high mechanical strength and are implantable. By combining this truly "bio" material with a textile-based assembly, this original tissue engineering approach is highly versatile and can produce a variety of strong human textiles that can be readily integrated in the body. Statement of Significance: Yarn of synthetic biomaterials have been turned into textiles for decades because braiding, knitting and weaving machines can mass-produce medical devices with a wide range of shapes and mechanical properties. Here, we show that robust, completely biological, and human yarn can be produced by normal cells in vitro . This yarn can be used as a simple suture material or to produce the first human textiles. For example, we produced a woven tissue-engineered vascular grafts with burst pressure, suture retention strength and transmural permeability that surpassed clinical requirements. This novel strategy holds the promise of a next generation of medical textiles that will be mechanically strong without any foreign scaffolding, and will have the ability to truly integrate into the host's body. Graphical abstract: Image, graphical abstract